No, it's not magic. It's the future of iPhone Apptitude. - Stern, Zack.
Take two parts real-world imagery, and mash it up with one part digital data. Welcome to augmented reality apps. prepare to be awed.
Keywords: Iphone (Smartphone); Digital data